Constantin V. Gheorghiu, An answer to a proposed analysis - Avramov, Theodor (Forum Theologicum Sardicense, 2025)
Theodor Avramov, Constantin V. Gheorghiu, An answer to a proposed analysis. The author aims to respond to recent scholarship on Virgil Gheorghiu and his ideological and political conceptions. Key aspects of Gheorghiu’s system are highlighted and compared with interpretations by him and contemporary scholars. Based on this analysis, a proposal is made for the overall methodology of such studies.